THU0343 Metabolic syndrome and its components in fibromyalgia patients. (23rd January 2014) - Ursini, F.; Naty, S.; Calabria, M.; Labonia, M.; Grembiale, R.D.
Abstract : Background: Fibromyalgia is a chronic disorder of uncertain aetiology, characterized by widespread pain, muscle tenderness and decreased pain threshold to pressure and other stimuli. Metabolic syndrome is a complex entity, characterized by the clustering of different cardiovascular risk condition such as atherogenic dyslipidemia, high blood pressure, visceral obesity and abnormal glucose metabolism. Aim of this work is to investigate the prevalence of metabolic syndrome in fibromyalgia patients. Objectives: Objective of our study was to evaluate the prevalence of metabolic syndrome (MS) and its components in fibromyalgia patients. Methods: For the present study 97 consecutive fibromyalgia female patients referred to the Internal Medicine Unit, University of Catanzaro (Italy) for chronic widespread pain were recruited. Fibromyalgia was diagnosed by a single specialist according to 1990 American College of Rheumatology (ACR) Criteria [1]. The presence of Metabolic Syndrome (MetS) was defined according to the American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) criteria [2]. These criteria define the presence of the MetS if three of the five following features are present: (1) Waist circumference ≥102 cm in men and ≥88 cm in women; (2) fasting triglycerides, ≥150 mg/dL or drug treatment for elevated triglycerides; (3) reduced high-density lipoprotein cholesterol (HDL-C), <40 mg/dL) in men and <50 mg/dL) in women, or drug treatment for reduced HDL-C; (4) blood pressure, ≥130 mmHg systolic blood pressure (SBP) or ≥85 mmHg diastolic blood pressure (DBP) or antihypertensive drug therapy; (5) fasting glucose, ≥100 mg/dL or drug treatment for hyperglycemia. Results: The mean age was 51.9±9.0 years with a range from 32 up to 76 years. In our population, the prevalence of metabolic syndrome (MS) diagnosed according to AHA/NHLBI Guidelines was 39.77%, with 41 out of 97 patients fulfilling at least three of the five features needed for diagnosing the syndrome. Of our 41 patients diagnosed with metabolic syndrome (MetS+ group), 24 patients had three features, 14 patients had four, and 3 patients had five features. In the remaining patients (MetS- group), 22 had two features while only 6 had one feature and none had zero features. Elevated waist circumference was found in 66/97 (64.02%) patients; elevated triglycerides in 33/97 (32, 01%) patients; reduced HDL-cholesterol in 18/97 (17.46%) patients; elevated blood pressure 69/97 (66.93%); elevated fasting glucose in 31/97 (30.07%). As expected, compared to the MetS-, MetS+ patients had a higher BMI (30.9±4.9 Vs 27.5±4.5, p=0.002), fasting glucose (99.8±13.6 Vs 89.1±10.1, p<0.0001) and fasting insulin levels (15.3±9.7 Vs 9.5±4.6, p=0.0001). The number of positive tender points was significantly higher in MetS+ group (p=0.01), while no statistical significant differences were found in ESR (p=0.28) or CRP (p=0.32) in MetS+ Vs MetS- patients. Conclusions: Female patients with fibromyalgia have increased prevalence of MetS. On the basis of our data and literature evidences seems plausible that increased prevalence of MetS in patients with fibromyalgia is mainly due to an increased prevalence of high blood pressure and visceral obesity. Disclosure of Interest: None Declared